Highly Stretchable, Hysteresis-Free Ionic Liquid -Based Strain Sensor for Precise Human Motion Monitoring - Choi, Dong Yun; Kim, Min Hyeong; Oh, Yong Suk; Jung, Soo-Ho; Jung, Jae Hee; Sung, Hyung Jin; Lee, Hyung Woo; Lee, Hye Moon (American Chemical Society, 2017)
A highly stretchable, low-cost strain sensor was successfully prepared using an extremely cost-effective ionic liquid of ethylene glycol/sodium chloride. The hysteresis performance of the ionic-liquid-based sensor was able to be improved by introducing a wavy-shaped fluidic channel diminishing the hysteresis by the viscoelastic relaxation of elastomers. From the simulations on visco-hyperelastic behavior of the elastomeric channel, we demonstrated that the wavy structure can offer lower energy dissipation compared to a flat structure under a given deformation. The resistance response of the ionic-liquid-based wavy (ILBW) sensor was fairly deterministic with no hysteresis, and it was well-matched to the theoretically estimated curves. The ILBW sensors exhibited a low degree of hysteresis (0.15% at 250%), low overshoot (1.7% at 150% strain), and outstanding durability (3000 cycles at 300% strain). The ILBW sensor has excellent potential for use in precise and quantitative strain detections in various areas, such as human motion monitoring, healthcare, virtual reality, and smart clothes.
Keywords: CARBON NANOTUBES; ELASTOMERS; SKIN; TRANSPARENT; ELECTRONICS; DESIGN; SOFT; COMPOSITES; NETWORKS; FILMS